2004
DOI: 10.1081/00268970410001728573
|View full text |Cite
|
Sign up to set email alerts
|

Hyperdeterminantal calculations of Selberg's and Aomoto's integrals

Abstract: The hyperdeteminants considered here are the simplest analogues of determinants for higher rank tensors which have been defined by Cayley, and apply only to tensors with an even number of indices. We have shown in a previous article that the calculation of certain multidimensional integrals could be reduced to the evaluation of hyperdeterminants of Hankel type. Here, we carry out this computation by purely algebraic means in the cases of Selberg's and Aomoto's integrals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Note that J.-Y. Thibon with one of the authors have already investigated the links between combinatorics and Selberg integrals [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…Note that J.-Y. Thibon with one of the authors have already investigated the links between combinatorics and Selberg integrals [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…This kind of hyperdeterminant have been already considered by the authors in collaboration with Thibon and Belbachir [19,20,2]. In particular, it is shown that the coefficients C λ (n, l) arising in the expression…”
Section: Staircase Macdonald Polynomialsmentioning
confidence: 90%
“…The polynomial considered here is the simplest one in the sense that it generalizes the expansion of determinant as an alternated sum. Reader can refer to [19,20,21,23,26] for more informations on the subject.…”
Section: Staircase Macdonald Polynomialsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the authors investigated such polynomials in relation with the Selberg integral [22,23]. Without lost of generality, we will consider the polynomials…”
Section: Definitions and General Propertiesmentioning
confidence: 99%